1998
DOI: 10.1093/oxfordjournals.jbchem.a022211
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Principal mRNA Species for Human 3 -Hydroxysteroid Dehydrogenase Isoform (AKR1C3) That Exhibits High Prostaglandin D2 11-Ketoreductase Activity

Abstract: Human 3alpha-hydroxysteroid dehydrogenase exists in four isoforms, which belong to the aldo-keto reductase (AKR) superfamily and are named AKR1C1-AKR1C4. The properties of AKR1C3 have not been fully characterized compared to the other isoforms. In addition, a cDNA that shows more than 99% homology with AKR1C3 cDNA has been cloned from human myeloblasts. We have here expressed and purified a recombinant enzyme (designated as DBDH) from this cDNA. DBDH oxidized xenobiotic alicyclic alcohols and 3alpha- or 17beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(146 citation statements)
references
References 0 publications
4
141
0
Order By: Relevance
“…The activities to oxidize these synthetic substrates were inhibited by bile acids (data not shown), similarly to the previous report with BABP puri®ed from the liver (Hara et al 1996). On the other hand, PGFS shows prominent PGD 2 11-ketoreductase activity to reduce PGD 2 and to oxidize 9a, 11b-PGF 2 (Matsuura et al 1998;Suzuki-Yamamoto et al 1999). DD4 possessed 3a-HSD activity, such as the reduction of androstanolone and the oxidation of dihydroandrosterone and bile acids, including chenodeoxycholic acid.…”
Section: Substrate Speci®city Of Human 20a-hsd and Three Akrssupporting
confidence: 88%
“…The activities to oxidize these synthetic substrates were inhibited by bile acids (data not shown), similarly to the previous report with BABP puri®ed from the liver (Hara et al 1996). On the other hand, PGFS shows prominent PGD 2 11-ketoreductase activity to reduce PGD 2 and to oxidize 9a, 11b-PGF 2 (Matsuura et al 1998;Suzuki-Yamamoto et al 1999). DD4 possessed 3a-HSD activity, such as the reduction of androstanolone and the oxidation of dihydroandrosterone and bile acids, including chenodeoxycholic acid.…”
Section: Substrate Speci®city Of Human 20a-hsd and Three Akrssupporting
confidence: 88%
“…This effect is reflected by the lower K I for indomethacin observed for both the uncompetitive inhibition of PQ reduction and the competitive inhibition of testosterone oxidation as compared to the higher K I value observed for the competitive inhibition of Δ 4 -androstene-3,17-dione reduction. Inhibition of the AKR1C3-mediated formation of the PGF 2 isomers by indomethacin and its analogues may occur through either one or both of these complexes as these reactions have catalytic efficiencies that are intermediate between the reduction of PQ and the reduction of Δ 4 -androstene-3,17-dione [10].…”
Section: Discussionmentioning
confidence: 99%
“…Indomethacin methyl ester, which could only be tested up to 20 μM because its UV absorbance interfered with the assay at higher concentrations, effectively inhibited only AKR1C3 and had no effect on PQ reduction by the other AKR1C enzymes at the concentrations tested. Previously, Matsuura et al [10] had shown that indomethacin had high affinity for AKR1C3, while Hara et al [26] showed that indomethacin was a relatively weak inhibitor of AKR1C1 and AKR1C2. However, these studies used widely varied concentrations of substrate relative to the K M of the respective enzymes, making the results difficult to compare across isoform.…”
Section: Inhibition Of Akr1c-mediated Pq Reduction By Nsaids and Indomentioning
confidence: 99%
See 1 more Smart Citation
“…AKRs that have hydroxysteroid dehydrogenase activity can either form or eliminate active steroid hormone in target tissues and therefore may regulate the occupancy and ^raws-activation of steroid receptors (54). A similar case could be made for AKRs that have prostaglandin reductase activity since they may regulate ligand access to PPARy receptors (55). This area needs further attention.…”
Section: Future Directionsmentioning
confidence: 99%